Analisis Potensi Energi Osmosis sebagai Sumber Energi Terbarukan Inovatif: Analisis Bibliometrik - Bintang Bintang Bintang (Jurnal Teknik Mesin dan Pembelajaran, 2026)
Abstract This study aims to analyze the potential of osmotic energy (blue energy) as an innovative renewable energy source using a bibliometric approach. Data were collected from the Scopus database covering the period 2015–2025 and analyzed using VOSviewer and Bibliometrix software. The results indicate a significant increase in research on salinity gradient energy in recent years, with a primary focus on membrane material development for pressure retarded osmosis (PRO) and reverse electrodialysis (RED) technologies. Scientific production is dominated by countries such as China, India, and the United States, highlighting global disparities in research capacity. Furthermore, thematic mapping reveals that existing studies remain fragmented and lack comprehensive integration, particularly in terms of economic feasibility and large-scale implementation. Despite its strong potential as a stable and environmentally friendly energy source, osmotic energy development still faces considerable technical and economic challenges.